IMPLEMENTASI CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN AKIDAH AKHLAK UNTUK MENINGKATKAN PEMAHAMAN NILAI-NILAI KEISLAMAN SISWA MAS MIFTAHUSSALAM - Alya Salsabila; Muhammad Yunan Harahap; Hadi Saputra Panggabean (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to describe in detail how the contextual approach is applied in teaching Akidah Akhlak (Islamic morals) in madrasahs, as well as to reveal its profound influence on students' understanding of Islamic values. This study is based on a qualitative approach with a careful and scientific descriptive study style. Data sources were obtained from the head of the madrasah, teachers of the Akidah Akhlak subject, and twelfth-grade students who are at the heart of the learning process. Data collection was conducted through direct observation, in-depth interviews, and comprehensive documentation. All data obtained were analysed using Miles and Huberman's interactive analysis model, which includes data reduction, presentation of results, and drawing of meaningful conclusions. The implementation of a contextual approach in teaching Islamic beliefs and morals at Miftahussalam Private Senior High School (MAS) has proven effective in strengthening students' understanding of Islamic values. By linking lesson material to everyday realities, this approach guides students to go beyond merely memorising theological concepts to actually putting them into practice, such as in dealing with issues of tolerance, honesty, and social responsibility. Evaluation results show a significant increase in learning completeness and positive attitudes among students towards Islamic values, confirming that the contextual approach plays an important role in shaping a strong and meaningful religious character.